Physical Education and Disabilities in Brazilian Periodics (1979 To 2017): A Look at the Non School Context (Global Journal of Human-Social Science, 2022)
This study aimend to identify undertand and problematize the meanings attributed by the production of knowledge in Physical Education PE in relation to the discussions about the issue of disability between the period from 1979 to 2017 Methodologically it consists of a bibliographical research and of quantitative-qualitative approach based on the correlation of bibliographical and documentary sources
Keywords: disabilities; physical education; literature review; athletic performance